Sequential surgical steps for conservative management of Morbidly Adherent Placenta: Case series - Abo Bakr A. Mitwaly; Ahmed M. Abbas (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:Cesarean section rates are increasing with associated increase in placenta previa and accreta. Placenta accreta is a major cause of maternal morbidity and mortality. Our objective was to evaluate of a new method of combined surgical steps in management of morbidly adherent placenta (MAP) to face its burden, psychological and marital disintegration if managed by hysterectomy in our low facilities.Materials and Methods:In this case series, we evaluated the use of sequential surgical steps for conservative management of 20 cases of MAP as regard the intra-operative and post-operative outcomes in Assiut Women Health Hospital, Egypt from June to December 2014. The sequential steps started by perfect dissection of urinary bladder, then delivery of the fetus followed by exteriorization of the uterus and application of 4 ring forceps on both uterine and ovarian vessels. Trial of placenta removal followed by application of two towels in the uterine cavity to achieve hemostasis. Ligation of uterine artery bilaterally at double low level. Finally, plication of the friable lower uterine segment from anterior wall after removal of towels.Results: The mean age of the included women was 29.95±4.8 years. All cases had previous uterine scar and placenta previa. Ten cases (50%) had placenta accreta, 8 cases (40%) had placenta increta and 2 cases had placenta percreta. Our procedure was succesfulin all 18 cases of placenta accreta and increta but 2 cases of placenta percreta required hysterectomy. No postpartum hemorrhage in all cases. There were no maternal deaths.Discussion:This new method was favorable in the management of MAP and decreased the incidence of hysterectomy in cases of placenta accreta and increta.